KEBUDAYAAN ANGKLUNG BANYUMAS TERKAIT BABAD BANYUMAS - Arina Dyah Suryani, Arina; Putri Ryolita, Widya (Universitas Hasanuddin, 2023)
The angklung tradition in Banyumas is closely related to the Babad Banyumas, an ancient text that contains the history and myths of the Banyumas area. In the Banyumas Chronicle, the angklung is considered a sacred musical instrument that has magical powers. This musical instrument is often used in traditional ceremonies and religious rituals in Banyumas. The beliefs and culture of the Banyumas people associate angklung with a spiritual power that can unite energy. The Banyumas angklung tradition involves the community or angklung music groups consisting of angklung players and drummers. They train together to protect and preserve the angklung cultural heritage in Banyumas. This study explores the relationship between the angklung tradition in Banyumas and the Banyumas Chronicle. The results of this study are about the Banyumas angklung tradition and its relationship with the Banyumas Chronicle. Kata Kunci : Angklung Tradition, Banyumas, Banyumas Chronicle, History and myth,Aspects of community life.